The economics of Irish forestry - Gray, H. J. (Statistical and Social Inquiry Society of Ireland, 1964)
In reviewing the development of State Forestry in Ireland with particular regard to its economic implications, I propose to deal successively with three main periods of development?-1908-1922 and 1922-1958?which between them constitute the first half-century of State forest development and, finally, the period from 1958 onwards.
Read before the Society, 20 December 1963
Keywords: Forestry; Irish forestry; Agriculture; 314.15